Rancang Bangun Sistem Pelacakan pada Penyewaan Sepeda Motor Menggunakan GPS Berbasis Internet of Things - Zikri Rahman; Ratna Aisuwarya; Rifki Suwandi (Universitas Andalas, 2023)
Motorcycles are a means of transportation that many people choose for daily transportation. This is because motorbikes are more effective and efficient than cars. However, the rate of loss of motorbikes continues to increase, especially for motorbikes that are rented out. By designing a system that can provide comfort to vehicle renters and increase security in opening a motorbike rental business. Therefore, a system is designed that can monitor the position of motorbikes that can be monitored through an Android application. The motorcycle will be installed with a tracking system using the GPS module, RTC module and nodemcu microcontroller. The GPS module functions to determine the coordinates of the motorbike's whereabouts and is displayed on an Android-based application and the RTC module is used for scheduling notification delivery in the form of messages to tenants when the rental time is up. The results of this study are that the android application can track the position of the motorbike and make it easier for motorbike rental business owners to work.